PEMETAAN STRUKTUR PENGETAHUAN DAN TREN PENELITIAN ENERGI AIR DALAM TRANSISI ENERGI BERKELANJUTAN: ANALISIS BIBLIOMETRIK - Hernita Zaida Nisrina; Rizky Setiawan Ramadhan; Ryan Adriansyah (Journal of Industrial Engineering & Technology Innovation, 2026)
This study aims to map the knowledge structure and research trends of water energy within the context of sustainable energy transition using a bibliometric analysis approach. The data were collected from the Scopus database, consisting of 2000 documents published between 2021 and 2026. The analysis was conducted using VOSviewer and RStudio (bibliometrix) to identify publication trends, scientific collaboration patterns, keyword structures, and thematic evolution. The results indicate a significant increase in water energy research, with dominant themes including renewable energy, hydrogen production, and sustainability. Network analysis reveals strong interconnections among topics, reflecting the multidisciplinary nature of the field. In addition, scientific collaboration is still dominated by developed countries, while research themes are shifting toward integration with technologies such as energy storage and electrolysis. This study contributes to understanding research development directions and supports future research strategies and sustainable energy policies.